The role of oxidative stress in senescence and immune responses of the mosquito "Aedes aegypti" - Belli, Alessandro (Neuchâtel : Université de Neuchâtel, 2023)
Oxidative stress arises from an imbalance between the production of free radicals and the body's capacity to counteract them with antioxidants. An excess of free radicals can lead to damage in various cellular components. Initially, free radicals were considered inherently toxic, and given their presence throughout Earth's history, Harman proposed that the accumulation of oxidative damage over time was the fundamental mechanism behind senescence (ageing). However, this theory relied heavily on evidence from studies comparing data across different species. As studies began to manipulate free radical production and antioxidant defences within the same species, contradictory results emerged. Consequently, we adopted an evolutionary approach to explore whether the accumulation of oxidative damage could account for senescence within a species where two populations had been selectively bred for varying lifespans. Regrettably, our experiment did not yield direct support for the free radical theory of ageing. The long-living mosquito lines did not exhibit significant differences in oxidative damage levels compared to the short-living lines. Nevertheless, our investigation revealed that mosquitoes with longer lifespans had lower levels of reactive oxygen species (ROS) and higher levels of antioxidant defences, resulting in a superior redox potential. This suggests that rather than oxidative damage, an individual's ability to maintain the balance between free radical production and antioxidant defences throughout its life may be the primary driver of senescence. Additionally, recent discoveries have unveiled the beneficial roles of ROS, which are essential for normal cellular metabolism. This paradigm shift led to a reevaluation of the role of free radicals in biology. We now understand that they are involved in several critical biological processes, such as cell proliferation, mobility, signalling, immunity, and more. However, it is crucial to recognize that while ROS play essential roles, they must be maintained within a narrow concentration range for their benefits to manifest. When employing them in their metabolic processes, organisms require effective defences against excessive ROS. Hence, our research aims to elucidate the role of antioxidant defences in the immune response of Aedes aegypti mosquitoes against the microsporidia parasite Vavrai culicis. Our study supports previous findings that ROS are vital for resistance against the parasite, and we also observed that individuals with higher levels of glutathione have a reduced probability of being infected by the parasite. Therefore, mosquitoes must produce ROS in sufficient quantities to have an effective immune response and possess robust antioxidant defences. Finally, we investigated whether oxidative stress could be a mechanistic link in trade-offs between various life history traits. We examined whether males' susceptibility to oxidative stress influences the cost of reproduction and whether intrasexual competition drives this trade-off. Our results demonstrated that male Aedes aegypti mosquitoes experienced higher mortality rates, reduced tolerance to bacterial infection, and increased oxidative damage when residing in a group dominated by females (24 females / 8 males). This suggests that oxidative stress is associated with the trade-off between reproduction and survival. However, the primary driver of this trade-off appears to be the act of mating itself, possibly due to the proteins males must transfer to females during copulation. In conclusion, our thesis emphasizes that merely assessing oxidative damage is insufficient to comprehend the role of oxidative stress in various life history traits. What holds greater significance is the maintenance of a delicate equilibrium between free radical production and antioxidant capacity throughout an organism's lifespan. This equilibrium seems to drive the emergence and evolution of diverse life history traits and tradeoffs.
Thèse de doctorat présentée à la Faculté des sciences de l’Université de Neuchâtel (Suisse) Membres du jury : Prof. Jacob Koella (directeur de thèse) Prof. Daniel Croll Prof. Thomas Flatt. Date de soutenance : Neuchâtel, le 11 septembre 2023
Keywords: Aedes aegypti; oxidative stress; free radical theory of ageing; life history theory; host’s immune response; longevity; cost of reproduction; Vavraia culicis